Highly Conductive Networks of Silver Nanosheets. Issue 14 (26th February 2022) - Kelly, Adam G.; O'Reilly, Jane; Gabbett, Cian; Szydłowska, Beata; O'Suilleabhain, Domhnall; Khan, Umar; Maughan, Jack; Carey, Tian; Sheil, Siadhbh; Stamenov, Plamen; Coleman, Jonathan N.
Abstract: Although printed networks of semiconducting nanosheets have found success in a range of applications, conductive nanosheet networks are limited by low conductivities (<10 6 S m −1 ). Here, dispersions of silver nanosheets (AgNS) that can be printed into highly conductive networks are described. Using a commercial thermal inkjet printer, AgNS patterns with unannealed conductivities of up to (6.0 ± 1.1) × 10 6 S m −1 are printed. These networks can form electromagnetic interference shields with record shielding effectiveness of >60 dB in the microwave region at thicknesses <200 nm. High resolution patterns with line widths down to 10 µm are also printed using an aerosol‐jet printer which, when annealed at 200 °C, display conductivity >10 7 S m −1 . Unlike conventional Ag‐nanoparticle inks, the 2D geometry of AgNS yields smooth, short‐free interfaces between electrode and active layer when used as the top electrode in vertical nanosheet heterostructures. This shows that all‐printed vertical heterostructures of AgNS/WS2 /AgNS, where the top electrode is a mesh grid, function as photodetectors demonstrating that such structures can be used in optoelectronic applications that usually require transparent conductors. Abstract : This paper describes the printing of silver nanosheets to yield conductive networks. These networks display conductivities of 6 × 10 6 S m ‐1 under ambient processing, two orders of magnitude higher than graphene networks. After annealing, the conductivity surpasses 10 7 S m ‐1, competitive with the best printed conductors. Such networks are exceptional electromagnetic shields and can be utilized as electrodes in printed devices.